Work Readiness and Job Satisfaction of Youth with Intellectual Disabilities Participating in a Supported Employment Program - Hannah Branch (Undergraduate Research Journal for the Human Sciences, 2024)
A summer supported employment program was provided by a vocational rehabilitation agency to prepare transition-aged youth with intellectual disabilities for the workforce. This study examined the views of youth with intellectual disabilities on their pre-post-program work readiness and job satisfaction using survey methodology. Although youth seemed satisfied with their jobs, they reported no significant change in their perceived job readiness, and their job coaches also reported similar perceptions. As a summer program, the duration may not have been adequate to increase youth’s views of their work readiness. For summer supported employment programs, obtaining youth participant insight and feedback, although sometimes a challenging task, can assist in making program refinements.
Keywords: intellectual disabilities; work readiness; youth; vocational rehabilitation; supported employment; job satisfaction